LEGITIMASI PEMUNGUTAN JIZYAH DALAM ISLAM: OTORITAS AGAMA DAN PENGUASA - Dedy Sumardi (Media Syari'ah, 2017)
Jizyah is obliged to Non Muslim ahl dhimmah status as a voluntary compensation for protection both internally and externally. The legitimacy of the poll voting procedures derived from sources "religious" is the Qur'an, Hadith, and ijma ', and not as a ruling authority. The state has the authority to set the revenue from jizyah limited to the issue of voting systems and mechanisms. In practice, the poll voting procedures has been a shift and change in patterns over time. At the time of the prophet., The hallmark of the collection is a simple poll. While on the leadership of Umar bin Khatab friend, poll voting authority granted to the province and is fully accountable to the central government. Results of voting poll distributed to all public sector priorities based on community needs that can not be financed by the proceeds of zakat.